LEADERSHIP STYLES AND THEIR IMPLICATIONS FOR PROSPEROUS INDUSTRIAL RELATIONS IN NIGERIA - Kabiru Ishola, Genty (European Scientific Journal, ESJ, 2014)
Industrial relations as a profession or discipline of study have undergone a series of developmental stages. This is as a result of changing in world of work prompted by globalisation and its accomplice like technical innovation, knowledge economy to mention few. Thus, trade unions today face simultaneously a wide range of often contradictory tasks. Therefore, they need to change and are changing in order to meet both new and persistent challenges to their advancement of social justice, income security and industrial democracy. The study examines how trade union leaders are going to survive in this turbulent economy paradigm using effective leadership styles that promote prosperous industrial relations in Nigeria. The study adopted discourse content analysis using secondary information of existing literatures on the subject matter to draw up a concrete conclusion with the aid of pictorial discussion. The study concluded that all the styles of leadership can enhance prosperous industrial relations but recommended the need for a situational approach to leadership. That is, the best style of leadership will depend upon the situation. Again, it is important to note that genuine leadership can only turn things around with the cooperation of followership. Therefore, a successful leader is the one which employs all forms of leadership styles in a given situation with predominate cooperation from its followership.